Once upon an Eid : stories of hope and joy by 15 Muslim voices - Saeed, Aisha; Ali, S. K.; Alfageeh, Sara (Amulet Books, 2020)
Contains a collection of fifteen short stories about the Muslim holiday, Eid, and the themes around it such as hope, joy, and family. Includes black-and-white illustrations.